(untitled) (DIGITAL TRANSFORMATION AND ARTIFICIAL INTELLIGENCE, 2024)
Creative abilities play a pivotal role in a child’s cognitive development, influencing their problem-solving skills, adaptability, and future success. This study aimed to explore the factors that affect creative abilities in children through the analysis of correlation coefficients. The correlation coefficient of the influencing factors for the creative ability to master activities, knowledge, understanding Creative abilities play a pivotal role in a child’s cognitive development, influencing their problem-solving skills, adaptability, and future success. This study aimed to explore the factors that affect creative abilities in children through the analysis of correlation coefficients. The correlation coefficient of the influencing factors for the creative ability to master activities, knowledge, understanding at the stage of development of the child’s knowledge was studied, evaluation method and algorithm were developed. parameters selected as factors influencing children’s creative ability the power to monotonically influence the outcome was measured. parameters are processed according to the Likert scale, the formulas of the correlation coefficient were used to calculate the influence of the matrix on the matrix. The correlation coefficient analysis revealed substantial influences of age, interest in activities, teacher’s skills, and family environment on children’s creative abilities. These factors demonstrated strong associations, emphasizing their significant impact on nurturing creative potential in children.at the stage of development of the child’s knowledge was studied, evaluation method and algorithm were developed. parameters selected as factors influencing children’s creative ability the power to monotonically influence the outcome was measured. parameters are processed according to the Likert scale, the formulas of the correlation coefficient were used to calculate the influence of the matrix on the matrix. The correlation coefficient analysis revealed substantial influences of age, interest in activities, teacher’s skills, and family environment on children’s creative abilities. These factors demonstrated strong associations, emphasizing their significant impact on nurturing creative potential in children.